Real-world safety of aliskiren in primary hypertension: A cross-database study - Meirong Shan; Qian Guo; Ruofei Li; Ni Li; Yanhua Fu; Huanyu Qi; Ge Zhang; Qian Wang; Xingli Xu; Jinchuan Lai (PLoS ONE, 2026)
Hypertension is one of the main causes of cardiovascular diseases worldwide, affecting over one billion people. Although aliskiren offers a valuable option for inhibiting the renin-angiotensin system, its safety profile in the real world remains insufficiently explored, especially for rare or under-recognized adverse events (AEs), which have not been fully clarified. Therefore, leveraging large-scale post-marketing surveillance data is crucial for identifying rare AEs and guiding safer clinical practice. This study aims to elucidate pharmacovigilance signals associated with aliskiren (an antihypertensive drug) by systematically analyzing the characteristics of adverse events (AEs) from the U.S. Food and Drug Administration (FDA) Adverse Event Reporting System (FAERS) database and WHO-VigiAccess database, which provides a reliable scientific basis for clinical practice and regulatory decision-making. We conducted a retrospective quantitative analysis of aliskiren-related AE reports from the aforementioned two databases, employing the Proportional Reporting Ratio (PRR), Reporting Odds Ratio (ROR), Bayesian Confidence Propagation Neural Network (BCPNN), and Multi-item Gamma Poisson Shrinker (MGPS) algorithms for signal detection. The results indicate that there were 5,596 and 5,549 aliskiren-related reports in the FAERS and WHO-VigiAccess databases, respectively. The median duration of these AEs during the observation period was 62 days, with an interquartile range (IQR) of 7–282 days. In both databases, signals for aliskiren were distributed across 28 System Organ Classes (SOCs), among which investigations, cardiac disorders, renal and urinary disorders, vascular disorders, and metabolism and nutrition disorders exhibited significant signals based on specific criteria applied across the four algorithms. A total of 607 preferred terms (PTs) with significant disproportionality signals were detected using the four algorithms, including potential AEs not previously well-documented, such as palpitations, myalgia, proteinuria, muscular weakness, pulmonary edema, and pollakiuria. This study not only confirms the known adverse reactions of aliskiren but also uncovers new potential risks, highlighting the importance of strengthening drug safety monitoring to enhance therapeutic efficacy and reduce the risk of adverse reactions. It provides valuable safety insights for physicians considering the use of aliskiren in the management of primary hypertension.